Level of adrenoreception and acetylcholine reception on lymphocytes in peripheral blood in patients with anterior uveitis complicated by macular edema - Храменко, Наталія Іванівна; Усов, Володимир Якович; Величко, Людмила Миколаївна; Богданова, Олександра Вікторівна; Коновалова, Наталія Валеріївна (My University, 2021)
The nervous system and immune system are two so-called „supersystems“ that play a vital role in achieving homeostatic adaptations to routine daily conditions and to challenging or adverse environmental conditions caused by injury, infections, and exposure to toxins (Elenkov et al., 2000). Imbalance of The ANS could be the result of chronic infammation, but conversely, it is also possible that changes in the ANS infuence infammation, disease development and severity (Koopman FA. et al., 2017). It is important to study the role of immunological changes in macular edema in anterior uveitis, because it is the main cause of vision loss in patients. Objective: To determine the level of expression of receptors for adrenaline and acetylcholine in the peripheral blood lymphocytes in patients with anterior uveitis (AU), complicated by macular edema (ME). Material and methods: The level of expression of receptors for adrenaline and acetylcholine on peripheral blood lymphocytes in patients with recurrent AU was studied using the immunocytochemical PAP method. Clinical and immunological studies were carried out during periods of remission and relapse in 28 patients with AU without complications and in 21 patients with AU with ME. Result: During the period of remission in patients with AU, the level of expression of adrenaline receptors on peripheral blood lymphocytes was 11.6±3.2 %; to acetylcholine–13.3±4.6 %; in the period of relapse to adrenaline–11.9±4.4 %, to acetylcholine–12.7±5.0 %. In patients with AU with ME during remission, the level of expression of receptors for adrenaline on peripheral blood lymphocytes is 13.0±2.5 %, for acetylcholine–13.0±1.4 %. During the period of relapse, the level of reception to adrenaline was 15.8±3.6 %, signifcantly higher than in patients without complications by 32.7 % (p=0.01); to acetylcholine–15.9±3.0 %, signifcantly higher, by 25.2 % (p=0.04). Conclusion: The studies have shown that during the relapse period in AU patients with ME, the level of expression of adrenaline receptors on peripheral blood lymphocytes is higher than in patients without complications.